ANALISIS ANTIBAKTERI PERUSAK MAKANAN KITOSAN KOMBINASI GAMBIR DAN GLUKOSA SEBAGAI PENGAWET ALAMI FUNGSIONAL UNTUK MAKANAN - Sari, Selly Ratna; Guttifera, Guttifera; Arafah, Elmeizy; Lestari, Siti; Putri, Rizki Eka; Saadah, Raudhatus; Sumsanto, Muhammad (Jurnal Perikanan Unram, 2024)
Indonesia are one of the countries that produces the largest shrimp and produces quite a lot of waste and can be an environmental pollution. One of the efforts is to make chitosan and modify chitosan into a preservative. This research purposed to reduce shrimp shell waste and optimize preservation that already has antibacterial and antioxidants as preservatives for food destroy bacteria (Pseudomonas aeroginosa) This Research was conducted to find the right formulation between glucose and gambir concentrations. The Experimental Design used was a complete Randomized Rancagan conducted with three groups. This research was conducted find the right formulation between glucose and gambir concentrations. The Experimental Design used was a complete Randomized with three groups. Treatmenta were gambir concentration (A): A1 = 2% (concentration of gambier) A2 = 4% (concentration of gambier) and A3 = 6% (concentration of gambier), using the same chitosan and glucose concentration of 1%. The research conducted made a solution of chitosan preservative a combination gambir and glucose as a natural preservative and antibacterial testing of food destruction in this case is the bacterium Pseudomonas aeroginosa. The test includes antibacterial analysis using the inhibitory power diameter (DDH). The largest diameter is A1 treatment: Chitosan 1%, Glucose 1%, Acetic Acid 1%, Gambir 2%. The highest inhibitoryis 26 mm so that the A1 treatment is the best treatment.